2009
DOI: 10.1007/s00066-009-1921-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adjuvant Radiotherapy on Mortality Differs According to Primary Tumor Location in Women with Node-Positive Breast Cancer

Abstract: Medial tumor location is a significant adverse prognostic factor that should be considered in treatment decision- making for women with ALN+ BC. Improved survival was observed with radiotherapy use in all subgroups, except in women with medial tumors with > or = 4 ALN+ treated with postmastectomy radiotherapy. These findings raise concern that the favorable effect of radiotherapy may be offset by excess toxicities in the latter subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…Tumour size, ER/PR status and ductal histology were also in keeping with the findings of other correlation studies [25,27]. We have previously reported the poorer prognosis associated with breast inner quadrant location [33]. The present study found a trend for a higher risk of PET-positive distant organs associated with medial/ central tumour location.…”
Section: Fig 2 Probabilities Of Nodal Involvement According To Pet Nsupporting
confidence: 92%
“…Tumour size, ER/PR status and ductal histology were also in keeping with the findings of other correlation studies [25,27]. We have previously reported the poorer prognosis associated with breast inner quadrant location [33]. The present study found a trend for a higher risk of PET-positive distant organs associated with medial/ central tumour location.…”
Section: Fig 2 Probabilities Of Nodal Involvement According To Pet Nsupporting
confidence: 92%
“…According to current guidelines, chest wall irradiation is indicated in patients with T3 or T4 tumors, node-positive disease, or in patients with marginal or incomplete resection [12,20]. The benefits of chest wall irradiation have been illustrated in many prospective trials and several metaanalyses [8,19,25,26]. It has, thus, been demonstrated that adjuvant radiotherapy reduces the risk of local relapse by approximately two-thirds ultimately improving long-term survival of the patients [7,19,23,2].…”
Section: Introductionmentioning
confidence: 99%
“…It conveyed, also to the nonradiation oncologist, the evidence supporting the multiple benefits of radiation treatment in terms of both local and locoregional tumor control and patient survival if radiotherapy is systematically included as an integral part of a multimodal treatment plan. Several recent studies have also found radiotherapy to have beneficial effects on the survival of breast cancer patients [15,25,26].…”
Section: Discussionmentioning
confidence: 99%